МОДЕЛЮВАННЯ АСИНХРОННИХ МАШИН У СКЛАДІ ЕЛЕКТРОМЕХАНІЧНИХ СИСТЕМ З УРАХУВАННЯМ ВТРАТ У СТАЛІ СТАТОРА - Попович, О.М.; Головань, І.В. (Інститут електродинаміки НАН України, Київ, 2024)
A comparative study has been conducted on methods for accounting for the influence of losses in the stator iron of squirrel-cage induction motors on the operating parameters. A comparison was made between reference data and calculation results of the nominal mode parameters of an asynchronous motor without considering losses in the stator iron and with their consideration using equivalent resistances connected in parallel to the motor, as well as equivalent circuits of losses in the stator. The effect of the ratio of active and inductive components of the load of equivalent stator loss circuits on the results of mathematical modeling has been investigated. The study was carried out based on a universal mathematical model of an asynchronous motor of electromechanical systems with an arbitrary stator winding scheme. An algorithm for determining and adjusting the parameters of the stator loss circuits during the integration of the differential equations of electrical and mechanical balance of the asynchronous motor to a steady-state value has been developed, based on the values of losses in the stator iron (depending on the induction and frequency) and the effective value of the current of the equivalent circuit. To ensure solution stability, the use of an iteration coefficient and discretization of resistance adjustment has been justified. The application of stator iron loss circuits in the mathematical model of an asynchronous machine in generator mode has been justified, when the use of parallel connected equivalent resistances contradicts the machine's energy diagram. References 10, figure 1, table 1.